IMPLEMENTASI PAJAK PENGHASILAN BERDASARKAN PERATURAN PEMERINTAH NOMOR 46 TAHUN 2013 (Studi pada UMKM di Jawa Tengah dan Daerah Istimewa Yogyakarta) - Faizara Prabantari; Moh Didik Ardiyanto (Diponegoro Journal of Accounting, 2017)
This study aims to determine differences income tax for individual taxpayer and corporate taxpayer refers to general rate based on Undang-Undang Nomor 36 Tahun 2008 that regulates about income tax for taxpayers and final rate based on Peraturan Pemerintah Nomor 46 Tahun 2013 that regulates about income tax for Micro, Small, and Medium Enterprises who has gross income until Rp 4.800.000.000 per year. The study also aims to determine the impact of Peraturan Pemerintah Nomor 46 Tahun 2013 for the individual taxpayer, corporate taxpayer, and for the government. Methods of data collection in this research is use a questionnaire that distributed to respondents (MSMEs) to answer questions pertaining on the application of Peraturan Pemerintah Nomor 46 Tahun 2013. The descriptive qualitative method is used to analyze the data. The results of the study found that: 1) There are differences in the amount of income tax expense to be paid using Undang-Undang PPh Nomor 36 Tahun 2008 and Peraturan Pemerintah Nomor 46 Tahun 2013 rates. Peraturan Pemerintah Nomor 46 Tahun 2013 will disadvantageous corporate taxpayers that have profit margin below 8% and will disadvantageous individual taxpayers that have profit margin below 7.91% for medium enterprises, 10.7% for small enterprises, as well as 40.3% for micro enterprises. 2) The data from questionnaire indicate that the majority of MSMEs which are in Central Java and Special Region of Yogyakarta with gross income until Rp 4.800.000.000 per year feel disadvantageous over PP 46/2013 and prefer to use UU 36/2008 rates. 3) Peraturan Pemerintah Nomor 46 Tahun 2013 is not in accordance with Daya Pikul Theory and some of the requirements in collecting taxes, among other justice requirement, and economic requirement. 4) The impact of PP 46/2013 implementation can advantageous taxpayers but will decrease tax revenue and can disadvantageous taxpayers but will increase tax revenues.